Common strategies in empirically supported psychological interventions for alcohol use disorders: A meta‐review. (22nd September 2022) - Nadkarni, Abhijit; Massazza, Alessandro; Guda, Rahul; Fernandes, Luanna T.; Garg, Ankur; Jolly, Mehak; Andersen, Lena S.; Bhatia, Urvita; Bogdanov, Sergiy; Roberts, Bayard; Tol, Wietse A.; Velleman, Richard; et al.
Abstract: Issues: Despite the large number of effective psychological interventions for alcohol use disorders (AUD), there is still a lack of clarity concerning the strategies that make these interventions effective. Approach: The overall goal of this review was to identify, examine and synthesise the information about common strategies from evidence‐based psychological interventions for AUDs by conducting a review of systematic reviews, that is, a meta‐review. We isolated the relevant primary studies from eligible systematic reviews and extracted information about the interventions from these studies to understand the strategies used. Analysis was restricted to narrative summaries. Key Findings: Thirteen reviews were eligible for inclusion in our meta‐review. Of these, eight demonstrated the effectiveness of a range of psychological interventions—behavioural couples therapy, cognitive behaviour therapy combined with motivational interviewing, brief interventions, contingency management, psychotherapy plus brief interventions, Alcoholics Anonymous and 12‐step treatment programs, family‐therapy or family‐involved treatment, and community reinforcement approach. The most commonly used component strategies in effective interventions for AUDs included assessment, personalised feedback, motivational interviewing, goal setting, setting and review of homework, problem solving skills and relapse prevention/management. Implications: Evidence about commonly used strategies in evidence‐based psychological interventions for AUDs offer the possibility of creating menu‐driven interventions that can be tailored to respond to individual client needs and preferences in different contexts.